Marianne Alberts (1928–2020) : caring, compassionate and humble biochemist and pioneer - Ramsay, Michèle (South African Journal of Science, 2021)
Refer to the document
Journal article published in South African Journal of Science 2021;117(3/4),
Keywords: Marianne Alberts; Orbituary; Biochemist; Orbituary; Alberts marianne, -- Prof, -- 1928-2020 . -- In memorium